Population‐Level Real‐World Healthcare Costs in Men and Women With Haemophilia A - Sam Hirniak; Samantha S. M. Drover; Andrea N. Edginton; Dagmar M. Hajducek; Alfonso Iorio; Mhd. Wasem Alsabbagh; William W. L. Wong (Haemophilia, 2026)
ABSTRACT Introduction Even with modern prophylaxis options, people living with haemophilia have significantly lower quality of life and joint health outcomes than those without. Aim Our goal was to determine if real‐world health‐system costs are higher for people living with haemophilia A compared to those without and determine how joint‐health state impacts this cost. Methods We utilized a population‐level, retrospective study design using health administrative data to determine the impact of sex and joint‐health states on cross‐sectional cost. Cases were identified using diagnostic codes. Joint health states were determined in 30‐day intervals by stepping forward and backward from joint replacement surgeries. Control groups were established through propensity score matching, aligning participants based on demographic, economic and health‐related variables. Direct 30‐day medical costs were generated in 2022 CAD. The impact of sex and disease health phases on direct healthcare system costs was analyzed through a two‐part regression model. Results 2341 eligible individuals with haemophilia A were identified. 26% were female. In pre‐severe joint damage, mean 30‐day costs were higher for patients with haemophilia A—$910 (standard deviation SD: $4069) for females and $724 (SD: $3577) for males, compared to $469 (±$2126) and $352 (±$2188) for matched controls, respectively. The regression model showed that current joint health state, number of other comorbidities, haemophilia status and sex were important factors within healthcare system cost. Conclusions The results of this study indicate that even with haemophilia treatment there remains an increased healthcare system cost for those with haemophilia A, regardless of sex.